A Systematic Review of the Causes and Management of Nonthrombotic Embolic Stroke of Tissue Origin. (24th April 2018) - Mello, Sarah; Judge, Ciaran; Kelly, Roisin; Bradley, David; Harbison, Joseph
Abstract : Introduction . Various bodily tissues have been reported to enter the arterial circulation and embolize to the brain resulting in ischemic stroke. Most frequently nonthrombotic embolic stroke (NTES) of tissue origin is iatrogenic or related to an underlying disease process. With the increase in elective surgery and intravascular procedures, NTES may increase in prevalence. Aim . To compile a summary of the background, incidence, presentation, and treatment of NTES of tissue origin, by conducting a systematic review of the current literature. Summary of Review . We searched EMBASE and MEDLINE for articles on NTES of tissue origin published in English with no restriction on publication date (search date June 2017). 800 articles were identified and screened and 159 articles were ultimately reviewed in full text and included in qualitative analysis. Articles deemed relevant were assessed by a second reviewer to confirm compatibility with the inclusion criteria. References of included articles were reviewed for relevant publications. We categorized the pathology of the emboli into the following groups: amniotic fluid (4 publications), tumour (60 publications), fat (43 publications), cholesterol (19 publications), and intravascular debris (12 publications). We then summarized the available literature on each cause of NTES. Conclusions . NTES of tissue origin is an uncommon but important diagnosis to consider particularly in younger stroke patients and in certain clinical settings. Treatment for NTES is currently anecdotal and based on small case series. Embolectomy may emerge as the therapy of choice due to the longer treatment timeframe and heterogeneity of the emboli.